2018
DOI: 10.36108/jrrslasu/8102/50(0120)
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of essential oils from Bambusa vulgaris Leaf (Fresh and Dried) Schrad. Ex J.C. Wendl. [Poaceae] obtained in Nigeria

Abstract: Essential oil is a hydrophobic concentrated liquid which contains volatile aroma compounds from plants. Bambusa vulgaris grows widely in the tropical and subtropical regions and has been reported to have different ethnomedicinal values such as antimalaria and antioxidant. It is also known to be an ornamental plant. The essential oil was extracted from both the fresh and dried leaves of Bambusa vulgaris by hydrodistillation method using a Clevenger apparatus. The chemical constituents of the essential oils were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…22 Validation results indicated that the RMSD values of the molecular docking performed in this study were 0 Å. Based on the binding affinity value, ligand with 21 the best value was sulfur pentafluoride (∆G=-8.0 kcal/ mol), squalene (∆G=-7.3 kcal/mol), 3-aminodibenzofuran (∆G=-7.1 kcal/mol), and 2-monolaurin (∆G=-5.5 kcal/mol). Meanwhile, clavulanic acid had a ∆G value of -5.7 kcal/ mol.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…22 Validation results indicated that the RMSD values of the molecular docking performed in this study were 0 Å. Based on the binding affinity value, ligand with 21 the best value was sulfur pentafluoride (∆G=-8.0 kcal/ mol), squalene (∆G=-7.3 kcal/mol), 3-aminodibenzofuran (∆G=-7.1 kcal/mol), and 2-monolaurin (∆G=-5.5 kcal/mol). Meanwhile, clavulanic acid had a ∆G value of -5.7 kcal/ mol.…”
Section: Discussionmentioning
confidence: 73%
“…Then, gas chromatography-mass spectrometry (GC-MS) and the identification of chemical compounds contained in the B. vulgaris leaves essential oil based on the retention index of each compound are carried out. 21 The molecular docking process was started with validation based on the RMSD value. The RMSD value is said to be good if <2 Å.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation